1998
DOI: 10.1046/j.1460-9568.1998.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic loss reflected by secretoneurin‐like immunoreactivity in the human hippocampus in Alzheimer's disease

Abstract: Secretoneurin is a recently described peptide derived by endoproteolytic processing from secretogranin II, previously named chromogranin C. In this study, we have investigated the distribution of secretoneurin-like immunoreactivity in the human hippocampus in controls and in Alzheimer's disease patients, and compared the staining pattern to that of calretinin. Secretoneurin-like immunoreactivity is present throughout the hippocampal formation. At the border of the dentate molecular layer and the granule cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 60 publications
3
18
0
3
Order By: Relevance
“…Thus, chromogranins may be valuable markers for hippocampal fiber systems. In addition to its presence in the mossy fiber system, secretoneurin may also be contained in associationall commissural fibers or in fibers arising from the supramammillary nucleus of the hypothalamus (both of which terminate in the inner molecular layer) (24-28) or in fibers projecting from the entorhinal cortex to the outer molecular layer (7,8,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chromogranins may be valuable markers for hippocampal fiber systems. In addition to its presence in the mossy fiber system, secretoneurin may also be contained in associationall commissural fibers or in fibers arising from the supramammillary nucleus of the hypothalamus (both of which terminate in the inner molecular layer) (24-28) or in fibers projecting from the entorhinal cortex to the outer molecular layer (7,8,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In several recent reports, chromogranin/SN proteins have been found to be closely correlated with synaptic disturbance caused by neuronal/ glial and inflammatory mechanisms in conditions such as Alzheimer disease (3)(4)(5). It has also been reported that SN can promote the neurite outgrowth of immature cerebellar granule cells (6).…”
Section: Introductionmentioning
confidence: 98%
“…Obecnie wiele badań dotyczy zmian w móz-gowiu związanych z chorobami neurodegeneracyjnymi. W przebiegu wielu chorób ośrodkowego układu nerwowego (OUN), kora mózgu, móżdżek oraz rdzeń kręgowy stanowią większość struktur wrażliwych na zmiany związane z redukcją liczby neuronów (8). Stan awitaminozy charakteryzujący się niedoborem witamin z grupy B, np.…”
Section: Praca Oryginalnaunclassified
“…Szczegółowe dane z dokonanych pomiarów w poszczególnych polach (19,20) wykazało, że w różnych obszarach układu limbicznego dochodzi do wzrostu liczby neuronów wraz ze wzrostem objętości komórek. Statystycznie istotne różnice parametrów morfometrycznych komórek piramidalnych w polach CA1-CA4 hipokampa wykazano u człowieka, psa, szczura oraz myszy (8,19,20,31). Neurony piramidalne w polach CA1-CA3 odgrywają istotną rolę w funkcjach hipokampa związanych z uczeniem się oraz pamięcią przestrzenną.…”
Section: Wyniki I Omówienieunclassified
See 1 more Smart Citation